Essential Urologic Laparoscopy The Complete Clinical Guide - Nakada, Stephen Y.; Hedican, Sean (Current Clinical Urology, 2010)
In Essential Urologic Laparoscopy: The Complete Clinical Guide, Second Edition, editors Sean P. Hedican and Stephen Y. Nakada provide a complete update of their critically acclaimed first edition while adding new material related to Hand Assisted Laparoscopic Radical Cystectomy, Laparoscopic Retroperitoneal Lymph Node Dissection and Laparoscopic Assisted Renal Ablation. The authors offer clear, concise chapters focusing on getting started, laparoscopic instrumentation, and step-by-step procedural adult laparoscopy. Each chapter is organized so that the reader can easily identify key points and pitfalls, providing user-friendly text that describes the essential equipment necessary for performing urologic laparoscopy. Authorative and highly practical, Essential Urologic Laparoscopy: The Complete Clinical Guide, Second Edition provides a comprehensive guide to performing effective and cutting-edge urologic laparoscopy and is a must have for any urologist looking to create, maintain, or expand a successful practice in minimally invasive urologic surgery.